Delays by patients in seeking treatment for acute chest pain: implications for achieving earlier thrombolysis. Issue 880 (1st February 1999) - Mumford, Andrew D; Warr, Kim V; Owen, Sandra J; Fraser, Alan G
Abstract : A study was set up to identify why patients delay seeking medical assistance after myocardial infarction. The study was performed in 100 consecutive patients with suspected acute myocardial infarction admitted to either the University Hospital of Wales, Cardiff, UK, or the Royal Jubilee Hospital, Victoria, British Columbia, Canada (50 patients from each centre). The main outcome measure was the delay from the onset of symptoms to admission to hospital. The mean total delay before admission was 385 minutes (SEM 45). The mean delay incurred by the patient in seeking assistance was 172 minutes (SEM 27), representing 45% of the total. Delay was longer in patients with crescendo angina and shorter in those later confirmed to have myocardial infarction. Patients with prior ischaemic heart disease (74% of patients) presented later than those with no such history. No other demographic or clinical factors predicted early or late presentation. Delays in seeking medical assistance after the onset of severe chest pain contribute significantly to total delays in patients' hospital admission and thrombolysis. The unexpected observation that patients with known ischaemic heart disease delay longer before seeking help in spite of their frequent contact with doctors, suggests that opportunities for educating patients are being wasted. Major efforts are needed to understand and modify behaviour of patients with chest pain to further reduce delays in treatment.